Odor-active compounds in cardboard - Czerny, Michael; Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2009)
The odor-active compounds of cardboard were identified by aroma extract dilution analysis and HRGC-MS analysis. In total, 36 compounds were detected with medium to high intensities during HRGC-olfactometry. The highest odor intensities were evaluated for vanillin, (E)-non-2-enal, (R/S)γ- nonalactone, 2-methoxyphenol, (R/S)-δ-decalactone, p-anisaldehyde, 3-propylphenol, and a woody-smelling unknown compound. Most of the identified compounds were described as odor-active cardboard constituents for the first time. Sensory experiments demonstrated that extensive release of odor-active compounds occurred upon moistening of the cardboard. Accordingly, data indicated that the odorants are present in cardboard in relatively high amounts. In a further sensory study, a transfer of the released odor to food was demonstrated In a model experiment showing that cardboards with high odor potential can cause unwanted flavor changes in foods. © 2009 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.llmch.odorac
Keywords: Aroma; Cardboard; Extract dilution analysis (AEDA); Odor; Odor threshold; Odorant transfer